Model of non-verbal component formation of intercultural competence in foreign students learning Russian as a foreign language - Stroganova, Kristina E. (Journal of the Belarusian State University. Journalism, 2019)
The article proposes a model for the formation of a non-verbal component of intercultural competence among Arab students in classes in Russian as a foreign language. The emphasis is directly on the non-verbal component of intercultural communication, which for the first time stands out in the structure of intercultural competence. Educational approaches, methodological principles, methods and stages of the formation of a non-verbal component of intercultural competence, as well as pedagogical conditions that will ensure its effective implementation and functioning, are proposed and scientifically substantiated.